Ծախսերի և ինքնարժեքի ձևավորման առանձնահատկությունները գինեգործության ոլորտում - Քնարիկ Հրահատի Խաչատրյան (ՀՀ ԳԱԱ հրատ.)
В статье целях исследования особенностей формирования затрат и себестоимости в сфере виноделия проведено исследование расходов и затрат, формирования себестоимости поэтапным способом и по экономическим элементам. В сфере виноделия задачи, поставленные перед действующими компаниями, с этой точки зрения можно разделить на две группы: совершенствование калькуляции расходов и совершенствование методологии учета и контроля. Поскольку производство продукции виноделия является поэтапным, то себестоимость на каждом этапе производства рассчитывается особо.To study the expenses and features of the prime cost in the winemaking, an analysis of the costs and expenses, was carried out in accordance with the stages method with respect to the investigation of the economic elements. In this regard, in the sphere of winemaking, the tasks for the existing companies are divided into the following two groups; improvement of cost calculation and development of the methodology of calculation and supervision. As the production of the wine-products is implemented on stage-by-stage basis, the prime cost in each stage is being calculated in consideration of the peculiarities of each stage.
Keywords: Հասարակական գիտություններ; Տնտեսագիտություն; Ֆինանսներ